Implementation and refinement of a surface model for heterogeneous HONO formation in a 3-D chemical transport model. (July 2015) - Karamchandani, Prakash; Emery, Chris; Yarwood, Greg; Lefer, Barry; Stutz, Jochen; Couzo, Evan; Vizuete, William
Abstract: The photolysis of nitrous acid (HONO) is a potentially significant daytime source of the hydroxyl radical, OH, one of the main chemical species that controls the oxidizing capacity of the atmosphere and plays an important role in ozone and PM2.5 formation. Research based on both field measurements and modeling has shown that HONO significantly affects the HOx budget in urban environments. Measurements during the Study of Houston Atmospheric Radical Precursors (SHARP) showed that radical production in the early morning in Houston was dominated by HONO photolysis. Field and laboratory studies suggest that nighttime heterogeneous conversion of NO2 on ground or aerosol surfaces, as well as daytime photolysis of HNO3 and NO2 adsorbed onto ground surfaces, can be important sources of HONO. Air quality models that only simulate homogeneous formation of HONO have been shown to substantially under-estimate observed HONO concentrations. Direct emissions of HONO also cannot explain the high HONO:NO2 ratios often measured in the boundary layer. These findings indicate that heterogeneous HONO formation plays an important role in the atmosphere. Previous approaches to include heterogeneous HONO formation in photochemical models have used surface to volume ratios to parameterize the chemistry on ground and aerosol surfaces. This paper describes the adaptation of a photochemical model to explicitly include a surface model that allows the treatment of the surface as a reservoir of deposited species that can be sorbed or penetrate into soils and vegetation, and undergo chemical degradation and transformation, and volatilization back into the air (re-emissions). The reactions in the surface model include HONO formation from thermal and photolytic reactions of deposited NO2 and HNO3 . The parameterizations for surface heterogeneous production of HONO are evaluated and refined using existing modeling databases for the Houston area during the SHARP study period. A companion paper describes the impacts of the new HONO formation pathways on radical sources and ozone chemistry in the Houston area. Highlights: New module to represent surface heterogeneous HONO formation in grid model. Addresses under-predictions of HONO concentrations by grid models. Model performance for HONO strongly dependent on performance for NO2 and HNO3 . Modeled HONO:NO2 and HONO:HNO3 ratios compare well with observed ratios. Approach provides framework for future refinement based on scientific advances.